Analisis SWOT Dalam Menentukan Strategi Pelatihan Keamanan Siber Dan Sandi - Agus Kurniati (Cendekia Niaga, 2019)
This study aims to identify strength and weakness (internal environment) and opportunity and threat (external environment) to formulate an appropriate strategy through SWOT analysis (Strengths, Weaknesses, Opportunities and Threats) in cyber security training at Training Center of National Cyber and Crypto Agency. This study used descriptive method, data collection through literature study, observation, interview and questionnaire. Data analysis technique is quantitative descriptive analysis technique. The result showed that using the SWOT analysis tool WO strategy had the highest score 3.97, SO strategy was ranked second with score 3, 76. Furthermore, WT strategy ranked third with score of 3.54 and ST strategy score 3.33. Strategies that can be carried out include SO Strategy: coordinating with stakeholders and meeting the competencies of all training staff, WO Strategy: revising the curriculum, increasing the number of teaching staff and developing competencies, ST Strategy: improving services and simplifying the training process, fulfilling the need of supporting equipment learning process, dissemination of training information, WT Strategy: establish cooperation with other training institutions, bring in instructors from outside and benchmark to other training institutions.